PFR2: a curated database of planktonic foraminifera 18S ribosomal DNA as a resource for studies of plankton ecology, biogeography and evolution. (15th April 2015) - Morard, Raphaël; Darling, Kate F.; Mahé, Frédéric; Audic, Stéphane; Ujiié, Yurika; Weiner, Agnes K. M.; André, Aurore; Seears, Heidi A.; Wade, Christopher M.; Quillévéré, Frédéric; Douady, Christophe J.; Escarguel, Gilles; et al.
Abstract Planktonic foraminifera (Rhizaria) are ubiquitous marine pelagic protists producing calcareous shells with conspicuous morphology. They play an important role in the marine carbon cycle, and their exceptional fossil record serves as the basis for biochronostratigraphy and past climate reconstructions. A major worldwide sampling effort over the last two decades has resulted in the establishment of multiple large collections of cryopreserved individual planktonic foraminifera samples. Thousands of 18S rDNA partial sequences have been generated, representing all major known morphological taxa across their worldwide oceanic range. This comprehensive data coverage provides an opportunity to assess patterns of molecular ecology and evolution in a holistic way for an entire group of planktonic protists. We combined all available published and unpublished genetic data to build PFR2, the Planktonic foraminifera Ribosomal Reference database. The first version of the database includes 3322 reference 18S rDNA sequences belonging to 32 of the 47 known morphospecies of extant planktonic foraminifera, collected from 460 oceanic stations. All sequences have been rigorously taxonomically curated using a six‐rank annotation system fully resolved to the morphological species level and linked to a series of metadata. The PFR2 website, available at http://pfr2.sb-roscoff.fr, allows downloading the entire database or specific sections, as well as the identification of new planktonic foraminiferal sequences. Its novel, fully documented curation process integrates advances in morphological and molecular taxonomy. It allows for an increase in its taxonomic resolution and assures that integrity is maintained by including a complete contingency tracking of annotations and assuring that the annotations remain internally consistent.